The Effectiveness of Taro Leaf Stalk (Colocasia esculenta L.) Ointment Extract on Burn Wound Healing in mice (Mus musculus L.) - Harlis, Wa Ode; Indrawati; Akbar, Moh. Djumadil (Proceeding International Conference on Religion, Science and Education, 2022)
The purpose of this study was to determine the effectiveness of taro leaf stalk extract ointment (Colocasia esculenta L.) on the length of time for wound healing, burn diameter, and percentage of burn healing in mice (Mus musculus L.). Taro leaf stalk extraction using the Maceration method. This type of research is experimental with a completely randomized design (RAL) method with 20 male mice divided into 5 treatment groups, namely Negative Control (Ointment Base), Positive Control (Bioplacenton 10%), K1 (Taro Leaf Stalk Extract Ointment 4%), K2 (Taro leaf stalk extract ointment 6%) and K3 (Taro leaf stalk extract ointment 8%), each with 4 replications. Making burns on the backs of mice with hot metal coins with a diameter of 20 mm which were affixed for 2 seconds. Observation parameters are the length of healing time, wound diameter, and percentage of burn healing for 18 days. Data were analyzed using One Way ANOVA (Analysis Of Variance) (? = 0.05%) and continued with the LSD (Least Significant Different) test. The results showed that taro leaf stalk extract ointment with a concentration of 8% was more effective in accelerating wound healing with an average healing time of 16 days compared to positive control (16.5 days), 4% ointment (17.25 days), 6% ointment (17 days) and negative control (18 days). The diameter of the burn which was initially 20 mm the fastest was 8% ointment with a wound diameter of 0.37 mm and a high burn healing rate of 98.12% when compared to Bioplacenton 10% followed by taro leaf stalk extract ointment with a concentration of 6% and 4%.